Thermal Stability of Octadecyltrichlorosilane and Perfluorooctyltriethoxysilane Monolayers on SiO(2) - Yang, Xiangdong (Nanomaterials (Basel), 2020)
Using in situ ultraviolet photoelectron spectroscopy (UPS) and X-ray photoelectron spectroscopy (XPS) measurements, the thermal behavior of octadecyltrichlorosilane (OTS) and 1H, 1H, 2H, and 2H-perfluorooctyltriethoxysilane (PTES) monolayers on SiO(2) substrates has been investigated. OTS is thermally stable up to 573 K with vacuum annealing, whereas PTES starts decomposing at a moderate temperature between 373 K and 423 K. Vacuum annealing results in the decomposition of CF(3) and CF(2) species rather than desorption of the entire PTES molecule. In addition, our UPS results reveal that the work function (WF)of OTS remains the same after annealing; however WF of PTES decreases from ~5.62 eV to ~5.16 eV after annealing at 573 K.